Perceived Impact of Socialization among Secondary Level Students in Pokhara (Journal of Development and Social Engineering, 2025)
Social studies courses have been one of the key courses in the school-level curriculum in Nepal. Among the major objectives of such courses is to promote socialization among the students. This descriptive study examines the students’ perception towards social studies courses and identifies the perceived impact of such courses on the level of socialization of the students in the Lekhnath area of Pokhara. By using a five-point Likert-scale questionnaire, data were collected from two hundred and two students of grade ten of two secondary schools in Lekhnath, one being public and another private one. The level of socialization was measured across multiple areas, including school, friendship, family, and sporting and cultural activities. These areas of activities were considered to measure the level of socialization of the students. Result indicate that more than half of the students (53.5%) have shown high-level of socialization. Friendship and family activities were considered highly positive by the students, whereas perception towards school clubs, formal meetings, digital engagement and cultural activities were reported comparatively weaker. Logistic regression results have shown that there is no statistically significant effect of age, caste, religion, and parental education on the level of socialization. However, father’s occupation, particularly in job and business category, tend to reduce the likelihood of higher level of socialization. The findings suggest the need of various practices and policy interventions to enhance the socialization role of social studies education in Nepal.